Microbiological and Physicochemical Characteristics of Three Types of “Soumbara” from Seeds of African Locust Bean in Korhogo Markets, Côte d’Ivoire - Ollo Kambire; Konan Mathurin Yao; Andrée Emmanuelle Sika; Aminata Coulibaly; Zamble Bi Irie Abel Boli; Rose Koffi-Nevry (International Journal of Food Science)
“Soumbara” is a fermented product sold in the markets of several West African countries. In the markets, it is sold in several formats (granulated, powder, and paste). The objective of this study was to evaluate the microbiological and physicochemical characteristics of these three types of “Soumbara” sold in the Korhogo markets. For this purpose, a preliminary survey followed by a sampling of 54 samples of “Soumbara” was carried out. The microorganism load count was carried out according to microbiological standards. The pH, titratable acidity, and moisture content were measured, respectively, with a pH meter, by dosing with sodium hydroxide solution and by differential weighing after passing the sample through the oven. The pH of the different samples is around 6. The moisture content is higher in “Soumbara” paste (20-24.7%) than in powdered (7.3-9.3%) and granulated (8.6-10.7%) “Soumbara.” The acidity rates are between 0.07 and 0.13%, 0.2 and 0.3%, and 0.08 and 0.1%, respectively, for the granulated, powder, and paste types. Mesophilic aerobic germ loads (6.17-8.38 log10 cfu/g) for all three types of “Soumbara” are above the standard. Total coliform (1.13-2.96 log10 cfu/g), mould (0.86-2.52 log10 cfu/g), and yeast (0.33-1.53 log10 cfu/g) loads are below standard. The microbiological quality of the three types of “Soumbara” is unsatisfactory. Overall, “Soumbara” powder is the most contaminated, followed by granulated and paste “Soumbara.” “Soumbara” must be added during culinary preparations in order to avoid possible public health problems.